Herd instinct, self-realization and Bildung - Ketovuori Mikko (Spain, 2022)
In recent years, research in arts education has expanded into new subject areas, such as environmental protection, minority issues and well-being, etc. The general impression in this debate seems to be that art is considered a panacea for all problems in society. It is noteworthy that the same topics are regularly featured on social media as well. It seems that the arts should follow their time rather than look to create something new on their own terms. Do the arts deserve their own ontology or are they just obedient servants of other things?
In this article we look at the ideas that have influenced perceptions of both the arts and humanity starting from the era of Enlightenment and Romanticism to postmodernism. Paradoxically, the long history of pronounced individuality and self-realisation has led a situation where collectivism and group thinking are taking society in an increasingly authoritarian direction. If emotions complement the prevailing rational and individual-centred person and the purely rational worldview, a new balance could help improve the "excessive use of imagination" of our time.
Conference Proceedings CIVAE 2022 : 4th Interdisciplinary and Virtual Conference on Arts in Education : May 11-12, 2022